Achieving a fine balance in mechanical properties and thermoelectric performance in commercial Bi2Te3 materials. Issue 10 (July 2020) - Zhu, Yu-Ke; Wu, Peng; Guo, Jun; Zhou, Yunxuan; Chong, Xiaoyu; Ge, Zhen-Hua; Feng, Jing
Abstract: Thermoelectric technology has been applied in the fields of industrial waste heat power generation, special spatial power supply, semiconductor chip cooling, advanced refrigeration, etc. Comparing to other thermoelectric material systems, bismuth telluride (Bi2 Te3 ) based thermoelectric materials are widely used in industrial and commercial fields due to their stable zT values and relatively high conversion efficiencies at room temperature range. However, the low hardness and easy dissociation of Bi2 Te3 materials lead to the waste of raw materials in industrial processing. Therefore, substantial efforts have been made to find a balance between the zT value and the hardness of bismuth telluride. In this study, the mechanical properties of commercial Bi2 Te3 were significantly enhanced by dispersing the second phase of the SiC particles in the matrix via a combined process of mechanical alloying (MA) and spark plasma sintering (SPS). Although the zT value of the composite was slightly decreased, the average hardness was increased from ~1.2 to 1.7 GPa, and the modulus of the composite was also improved. The thermal expansion rate and thermal expansion coefficients were also measured. The mechanism of the enhanced mechanical properties of the Bi2 Te3 was discussed in detail. This work offered a simple strategy for improving the machinability of commercial Bi2 Te3, which is of high importance for the large scale industrial application of thermoelectric materials.